Heterotypic tumor models through freeform printing into photostabilized granular microgels. (19th May 2021) - Molley, Thomas G.; Jalandhra, Gagan K.; Nemec, Stephanie R.; Tiffany, Aleczandria S.; Patkunarajah, Amrutha; Poole, Kate; Harley, Brendan A. C.; Hung, Tzong-tyng; Kilian, Kristopher A.
Abstract : We report the freeform printing of vessel structures and tumor aggregates within a granular suspension of cells and gelatin methacrylate microgels for modelling cancer progression and metastasis. Abstract : The tissue microenvironment contains a complex assortment of multiple cell types, matrices, and vessel structures, which is difficult to reconstruct in vitro . Here, we demonstrate model tumor microenvironments formed through direct writing of vasculature channels and tumor cell aggregates, within a cell-laden microgel matrix. Photocrosslinkable microgels provide control over local and global mechanics, while enabling the integration of virtually any cell type. Direct writing of a Pluronic sacrificial ink into a stromal cell-microgel suspension is used to form vessel structures for endothelialization, followed by printing of melanoma aggregates. Tumor cells migrate into the prototype vessels as a function of spatial location, thereby providing a measure of invasive potential. The integration of perfusable channels with multiple spatially defined cell types provides new avenues for modelling development and disease, with scope for both fundamental research and drug development efforts.